COVID-19: WHAT HAVE WE LEARNED SINCE THE BEGINNING OF THE EPIDEMIC UNTIL TODAY? - Milosevic, Ivana; Vujovic, Ankica (Srpski medicinski časopis Lekarske komore, 2021)
At the end of December 2019, in the city of Wuhan in China, the appearance of unknown viral pneumonia was recorded in a large number of patients. The cause of this infection was soon discovered - a new coronavirus, called SARS-CoV-2 due to its genetic similarity to the virus that causes severe acute respiratory syndrome (SARS-CoV). The infection has spread rapidly to other continents, and the pandemic is still ongoing. The clinical presentation varies from asymptomatic form, through symptoms of upper respiratory tract infection, to pneumonia and acute respiratory distress syndrome (ARDS). At the risk for severe disease are elderly, immunocompromised and chronic internist patients. The virus enters cells via angiotensin converting enzyme 2 (ACE2) receptor which is present in all tissues in the body. In addition to interstitial pneumonia, pathological changes are also found in other organ systems. The first case in Serbia was recorded on March 6, 2020. A large number of patients required the engagement of health workers of all profiles and the introduction of a large number of health institutions in the COVID system. The emergence of a new virus necessitated a new antiviral drug. Based on previous experience with the SARS-CoV virus, antiviral drugs known from before have been used, with varying degrees of success. The therapy changed in accordance with new knowledge, and since the beginning of the epidemic in Serbia, a National protocol for the treatment of COVID-19 has been established, which has kept pace with the recommendations of the world's leading institutions. The most significant event during the pandemic is the appearance of the vaccine against COVID-19 and vaccination in Serbia began in December 2020. The speed of pandemic completion depends directly on the speed and efficiency of vaccination, along with other epidemiological measures.
Keywords: coronavirus; COVID-19; pandemic; pneumonia